PENGARUH PROMOSI, INTENSITAS PERSIANGAN DAN KEBIJAKAN PRODUK TERHADAP KINERJA PEMASARAN BANDENG PRESTO PADA SENTRA USAHA BANDENG PRESTO KELURAHAN TAMBAKREJO SEMARANG - Listianto, Agil; Pradhanawati, Ari; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2014)
This study aims to determine the influence ofÂ  promotion, intensity of competition, and product policy on marketing performance bandeng presto. This type of research is explanatory research, with methods data collection using questionnaires and interviews. Sampling techniques using the technique of nonprobability sampling and samples are saturated. The sample in this research were 31 businessmen bandeng presto on Sentra Bandeng Presto. This research uses techniques of quantitative analysis. Quantitative analysis using the test of validity, reliability, regression analysis, the determination coefficient, test of significance (t-test).From the data analysis it can be conclude, that the indicate below entire partially independent variable, the variable promotion (X1) effect on the marketing performance (Y) amounted to 40,9%, intensity of competition (X2) effect on marketing performance marketing (Y) of 61,2%, and policy products (X3) effect on performance marketing (Y) of 54,9%.